Successful Sequential Treatment for Severe Asthma Coexisting COVID-19 via Budesonide/Glycopyrrolate/Formoterol Fumarate - Liang Y (International Journal of General Medicine, 2021)
Yingjian Liang,* Meizhu Chen,* Cuiyan Tan, Changli Tu, Xiaobin Zheng, Jing Liu Department of Pulmonary and Critical Care Medicine (PCCM), The Fifth Affiliated Hospital of Sun Yat-Sen University, Zhuhai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jing Liu; Xiaobin ZhengThe Fifth Affiliated Hospital of Sun Yat-Sen University, 52 East Meihua Road, Zhuhai City, 519000, People’s Republic of ChinaTel/Fax +86(0)7562528733Email liujing25@mail.sysu.edu.cn; zhxbin@mail.sysu.edu.cnAbstract: Awareness of the management of coronavirus disease 2019 (COVID-19) and airway diseases can effectively help clinical physician during the coronavirus pandemic. Herein, we elucidated a COVID-19 case coexisting with severe asthma. Budesonide/glycopyrrolate/formoterol fumarate (BGF) was used as sequential medicine to systemic glucocorticoids for his persisted symptoms related to bronchospasms. Our case suggests patients with long-term airway diseases like asthma probably attribute their symptoms to COVID-19 instead of primary diseases, which make it more difficult in the symptom control. BGF is able to be an effective and convenient choice as sequential medicine to systemic glucocorticoids in some refractory asthmatic patients complicated with COVID-19.Keywords: coronavirus disease 2019, asthma, budesonide/glycopyrrolate/formoterol fumarate, sequential treatment